A protective role of renalase in diabetic nephropathy. (17th January 2020) - Yin, Jianyong; Liu, Xuanchen; Zhao, Ting; Liang, Rulian; Wu, Rui; Zhang, Fangfei; Kong, Yiwei; Liu, Limei; Xing, Tao; Wang, Niansong; Zhao, Qing; Wang, Feng
Abstract: Renalase, a recently discovered secreted flavoprotein, exerts anti-apoptotic and anti-inflammatory effects against renal injury in acute and chronic animal models. However, whether Renalase elicits similar effects in the development of diabetic nephropathy (DN) remains unclear. The studies presented here tested the hypothesis that Renalase may play a key role in the development of DN and may have therapeutic potential for DN. Renalase expression was measured in human kidney biopsies with DN and in kidneys of db/db mice. The role of Renalase in the development of DN was examined using a genetically engineered mouse model: Renalase knockout mice with db/db background. The renoprotective effects of Renalase in DN was evaluated in db/db mice with Renalase overexpression. In addition, the effects of Renalase on high glucose-induced mesangial cells were investigated. Renalase was down-regulated in human diabetic kidneys and in kidneys of db/db mice compared with healthy controls or db/m mice. Renalase homozygous knockout increased arterial blood pressure significantly in db/db mice while heterozygous knockout did not. Renalase heterozygous knockout resulted in elevated albuminuria and increased renal mesangial expansion in db/db mice. Mesangial hypertrophy, renal inflammation, and pathological injury in diabetic Renalase heterozygous knockout mice were significantly exacerbated compared with wild-type littermates. Moreover, Renalase overexpression significantly ameliorated renal injury in db/db mice. Mechanistically, Renalase attenuated high glucose-induced profibrotic gene expression and p21 expression through inhibiting extracellular regulated protein kinases (ERK1/2). The present study suggested that Renalase protected against the progression of DN and might be a novel therapeutic target for the treatment of DN.